Prevalent zoonoses in Sao Paulo State, Brazil: the role of bats and molecular diagnosis - de França, Danilo Alves [UNESP]; Langoni, Helio [UNESP] (FapUNIFESP (SciELO), 2025)
This review explores the landscape of prevalent zoonotic diseases in Sao Paulo State, Brazil, focusing on the role of bats as reservoirs and the application of molecular biology in the diagnosis. The zoonoses covered include visceral and cutaneous leishmaniasis, Chagas disease, toxoplasmosis, bartonellosis, Q fever, Brazilian spotted fever, and leptospirosis. Molecular techniques can improve public health responses by accurately identifying pathogens and tracking their transmission dynamics in populations, thus enhancing early detection, characterization of strains, and monitoring of disease outbreaks. By elucidating the epidemiology and molecular aspects of zoonoses associated with bats in Sao Paulo State, we highlight the importance of integrated surveillance systems and multidisciplinary approaches to effectively manage and prevent these diseases.
Keywords: Infectious agents; Literature review; Reservoir; Surveillance; Zoonoses